Exact packing measure of central Cantor sets in the line - Garcia, I. (2012)
In this paper we consider a class of symmetric Cantor sets in R. Under certain separation condition we determine the exact packing measure of such a Cantor set through the computation of the lower density of the uniform probability measure supported on the set. With an additional restriction on the dimension we give also the exact centered Hausdorff measure by computing the upper density. © 2011 Elsevier Inc.